Investigating Vietnamese EFL university students’ critical thinking and Its relationship with argumentative writing : - Nguyễn, Sơn Tuyến (Trường Đại học Cần Thơ, 2020)
Critical thinking has been recognized as a key academic skill due to its role in the learning process, especially in higher education, and particularly in second and foreign language teaching and learning of writing. This thinking pattern is crucial in Vietnamese tertiary education since, in the globalized world of information, there has been an increased demand for students to gain greater depth of subject-specific knowledge and develop their ability to synthesize, process, and evaluate different sources of texts for the sake of meeting the needs of their academia and future studies. However, it is quite a new concept in the Vietnamese educational system; and few studies have been conducted to examine critical thinking in relation to argumentative writing. This thesis, henceforth, investigates the critical thinking ability of Vietnamese EFL (English as a foreign language) university students and its relationship with their writing argumentative essays. Data collected in this study include a questionnaire and an essay writing test. Participants were 126 EFL students at three universities in the Mekong Delta. The findings reveal that Vietnamese EFL university students’ critical thinking is at a high level while no significant relationship was observed between their critical thinking and their argumentative writing. The obtained results indicate that instructional methods and activities employed by Vietnamese EFL teachers in universities of the Mekong region may well promote the cognitive development of their students. It also suggests urgent actions from EFL teachers and stake-holders to seek feasible solutions to foster students’ implementation of their cognitive skills into their writing and other English language skills.